2010
DOI: 10.1111/j.1524-4725.2010.01723.x
|View full text |Cite
|
Sign up to set email alerts
|

Microcystic Lymphatic Malformation (Lymphangioma Circumscriptum) Treated Using a Minimally Invasive Technique of Radiofrequency Ablation and Sclerotherapy

Abstract: RFA ablates the lesions and achieves hemostasis while the sclerosant injected in and around the lesion reaches the deeper vascular lesions, preventing recurrence. The minimally invasive combination technique of RFA with sclerotherapy is a modality that can be used in the treatment of extensive microcystic malformations where surgical excision would lead to extensive scarring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 17 publications
0
22
0
2
Order By: Relevance
“…A study with direct puncture sclerotherapy using 20 mg/mL doxycycline reported complete ablation of 179 microcysts without presenting effectiveness per patient (8). As for sclerotherapy of microcystic LM, diverse levels of its effectiveness have been reported by lesion characteristics, treatment methods, sclerosants, and result evaluation criteria (5)(6)(7)(9)(10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…A study with direct puncture sclerotherapy using 20 mg/mL doxycycline reported complete ablation of 179 microcysts without presenting effectiveness per patient (8). As for sclerotherapy of microcystic LM, diverse levels of its effectiveness have been reported by lesion characteristics, treatment methods, sclerosants, and result evaluation criteria (5)(6)(7)(9)(10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Bu tedavi yaklaşımların birçoğundan derin komponentlere ulaşımdaki yetersizliği ve multifokal lezyonlara bağlı yüksek nüks oranları nedeniyle yüz güldürücü sonuçlar alınamamaktadır. 2,3,5,9 Tedavi seçeneğinin belirlenmesinde hastanın isteği, semptomların ciddiyeti ve merkezin deneyimi göz önünde bulundurulmalıdır. LS iyi huylu bir hastalık olarak bilindiğinden genellikle konservatif tedavi seçenekleri ön planda tutulmalıdır.…”
Section: Discussionunclassified
“…En düşük nüks oranlarının cerrahi ile olduğu bildirilmekle birlikte her hastada uygulanamayan ve sikatris bırakan bir yöntemdir [2][3][4] . Cerrahi dışındaki diğer tedavi seçenekleri arasında skleroterapi, radyoterapi, X ışınları, kriyoterapi, koterizasyon, radyofrekans enerjisi ve bazı lazerler bulunmaktadır 4,6 . Bu tedavi yaklaşımların birçoğundan derin komponentlere ulaşımdaki yetersizliği ve multifokal lezyonlara bağlı yüksek nüks oranları nedeniyle yüz güldürücü sonuçlar alınamamaktadır 3 .…”
Section: Discussionunclassified